Implementation of School Disaster-Safe Education Management Program at Senior High School in Batang Hari Regency - Masrianda Masrianda; Hadiyanto Hadiyanto; Sulistiyo Sulistiyo; Muspawi Muspawi; Sofwan Sofwan; Ali Ali (Universitas Muhammadiyah Enrekang, 2024)
This qualitative study employing a case study methodology aims to investigate and elucidate the execution of the Disaster Safe Education Unit Program management at SMA Zulhijjah in Batang Hari Regency. The participants in the research were twelve people. Interview data was analyzed using